Analysis of Students' Conceptual Understanding of Biology Material Based on STEM-Based Learning: (Analisis Pemahaman Konsep Mahasiswa Pada Materi Biologi Berdasarkan Pembelajaran Berbasis STEM) - Novallyan , Devie; Gusfarenie, Dwi; Safita, Reny (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2023)
The main objectives of biology learning are improving the mastery of concepts, understanding biology concepts in depth and applying them in problem solving processes. The aims of this research were to design a STEM-based Biology practicum module and evaluate its effectiveness on students' conceptual understanding. The method in this research followed a quasi-experimental research procedure, with a one group pretest and posttest design. This aims to obtain more information in understanding students' concepts after going through STEM-based biology practicum learning experiences. The research subjects were 36 junior high school students. Analysis of students' understanding of concepts is based on statistical descriptive data, normality test and paired t test and N-Gain. Based on the results of the research indicate that there is a significant effect of the application of STEM-based practicum modules on conceptual understanding. Besides that the N-Gain data shows an increase in students' understanding of concepts after being taught with the STEM-based biology practicum module. In this research, it has not specifically explained the model that is applied together with the STEM-based approach. It is important to do further research to design STEM-based learning with certain learning models. Key words: Conceptual understanding, Biology, STEM Abstrak. Tujuan utama pembelajaran biologi adalah meningkatkan penguasaan konsep, memahami konsep biologi secara mendalam dan menerapkannya dalam proses pemecahan masalah. Penelitian ini bertujuan untuk merancang modul praktikum Biologi berbasis STEM dan mengevaluasi keefektifannya terhadap pemahaman konsep siswa. Metode dalam penelitian ini mengikuti prosedur penelitian eksperimen semu, dengan one group pretest and posttest design. Hal ini bertujuan untuk memperoleh informasi lebih dalam memahami konsep siswa setelah melalui pengalaman pembelajaran praktikum biologi berbasis STEM. Subyek penelitian adalah 36 siswa SMP. Analisis pemahaman konsep siswa berdasarkan data statistik deskriptif, uji normalitas dan uji t berpasangan dan N-Gain. Berdasarkan hasil penelitian menunjukkan bahwa terdapat pengaruh yang signifikan penerapan modul praktikum berbasis STEM terhadap pemahaman konsep. Selain itu data N-Gain menunjukkan adanya peningkatan pemahaman konsep siswa setelah diajarkan dengan modul praktikum biologi berbasis STEM. Dalam penelitian ini belum secara khusus menjelaskan model yang diterapkan bersamaan dengan pendekatan berbasis STEM. Penting dilakukan penelitian lebih lanjut untuk merancang pembelajaran berbasis STEM dengan model pembelajaran tertentu Kata kunci: Pemahaman Konsep, Biologi, STEM